Creating Socioecological Novelty in Urban Agroecosystems from the Ground Up. (8th January 2018) - Egerer, Monika; Ossola, Alessandro; Lin, Brenda B
Abstract: The contemporary renaissance of urban agriculture is crucially linking ecological and social systems in modern cityscapes. Community gardens contribute ecological (biodiversity conservation) and social (food security) benefits to urban residents and enhance landscape multifunctionality. Cities have been recently labeled "novel ecosystems" because of the multiscalar interaction of sociocultural and biophysical elements. We conceptualize community garden soils within the novel ecosystem framework, arguing that gardeners are cultivating novel agroecosystems starting from their garden beds' soil. Although urban soil characteristics are linked to land-use legacies in most urban ecosystems, we find that in our system, the California central coast, community-garden soils may live outside the influence of legacies associated with geographic location. Instead, the intensive (re)working of soils by gardeners may washout legacy signals and decadal chronological trends, leading to soil homogenization that reduces the biophysical ties to the meters of earth below. Thus, socioecological novelty can be created in multiple forms in cities.